2013
DOI: 10.1103/physreve.88.013017
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian coherent structures separate dynamically distinct regions in fluid flows

Abstract: Using filter-space techniques, we study the scale-to-scale transport of energy in a quasi-two-dimensional, weakly turbulent fluid flow averaged along the trajectories of fluid elements. We find that although the spatial mean of this Lagrangian-averaged flux is nearly unchanged from its Eulerian counterpart, the spatial structure of the scale-to-scale energy flux changes significantly. In particular, its features appear to correlate with the positions of Lagrangian coherent structures (LCS's). We show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 23 publications
3
41
0
Order By: Relevance
“…It was found that shrink lines delineate regions where energy moves up and down the energy cascade. 46 …”
Section: Applications Of the Geometric Approachmentioning
confidence: 99%
“…It was found that shrink lines delineate regions where energy moves up and down the energy cascade. 46 …”
Section: Applications Of the Geometric Approachmentioning
confidence: 99%
“…FTLE and FSLE methods have seen wide usage in both experimental [37,38,39,40] and observational [42,43,47,83,84,85,46,49,50,51] contexts.…”
Section: Lcs Diagnostic Methodsmentioning
confidence: 99%
“…The key point is whatever the definitions of LCSs, their formulation is typically (with a few exceptions, such as, for example, the burning manifolds of [32,33,34,35,36]) based solely on the Lagrangian trajectories associated with (1), and the goal is to identify fluid parcel groups that behave similarly, and are thus 'coherent.' This has been a rich area of study using both experimental [37,38,39,40] and observational [41,42,43,44,45,46,47,48,49,50,51,52,53] data.…”
Section: Introductionmentioning
confidence: 99%
“…Lagrangian stretching and FTLEs have been used extensively to approximate the locations of barriers to the movement of non-reacting species [37][38][39][40] and are closely related to Lagrangian Coherent Structures, 41,42 which are also calculated using C t镁T t . FTLEs have also been considered in ARD systems.…”
Section: Introductionmentioning
confidence: 99%